Pelatihan Pengembangan Perangkat Pembelajaran Berbasis Diferensiasi Bagi MGMP IPA Kota Makassar - Ramlawati, Ramlawati; Army Auliah; Sitti Saenab; Sari, Nur Indah; Shoffan Fatkhulloh (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2025)
Training on developing differentiation-based learning tools for MGMP IPA Makassar City aims to improve science teachers' competence in preparing teaching modules and learner worksheets (LKPD). This training included 20 science teachers who were members of the Makassar City Science MGMP. This activity occurred in December 2024 at the FMIPA Campus of Makassar State University. The Differentiated Science Inquiry (DSI) learning model is the focus of development by implementing four levels of inquiry: Demonstrated Inquiry, Structured Inquiry, Guided Inquiry, and Self-Directed Inquiry. The methods applied in the training include material delivery, training in the preparation of tools, and evaluation of training results. The evaluation results showed a significant increase in science teachers' understanding of aspects of the preparation of LKPDs dan modules, including understanding differentiated learning, DSI learning models, and the characteristics of LPDs and teaching modules. The training participants also showed enthusiasm and gave positive feedback regarding the methods and materials presented. Thus, this training can increase teacher creativity in developing flexible science learning tools that fit students' needs to support the implementation of the Merdeka Curriculum.